Functional motor disorders associated with other neurological diseases: Beyond the boundaries of "organic" neurology. (2nd January 2021) - Tinazzi, Michele; Geroin, Christian; Erro, Roberto; Marcuzzo, Enrico; Cuoco, Sofia; Ceravolo, Roberto; Mazzucchi, Sonia; Pilotto, Andrea; Padovani, Alessandro; Romito, Luigi Michele; Eleopra, Roberto; Zappia, Mario; et al.
Abstract: Background and purpose: The aims of this study were to describe the clinical manifestations of functional motor disorders (FMDs) coexisting with other neurological diseases ("comorbid FMDs"), and to compare comorbid FMDs with FMDs not overlapping with other neurological diseases ("pure FMDs"). Methods: For this multicenter observational study, we enrolled outpatients with a definite FMD diagnosis attending 25 tertiary movement disorder centers in Italy. Each patient with FMDs underwent a detailed clinical assessment including screening for other associated neurological conditions. Group comparisons (comorbid FMDs vs. pure FMDs) were performed in order to compare demographic and clinical variables. Logistic regression models were created to estimate the adjusted odds ratios (95% confidence intervals) of comorbid FMDs (dependent variable) in relation to sociodemographic and clinical characteristics (independent variables). Results: Out of 410 FMDs, 21.7% of patients ( n = 89) had comorbid FMDs. The most frequent coexisting neurological diseases were migraine, cerebrovascular disease and parkinsonism. In the majority of cases (86.5%), FMDs appeared after the diagnosis of a neurological disease. Patients with comorbid FMDs were older, and more frequently had tremor, non‐neurological comorbidities, paroxysmal non‐epileptic seizures, major depressive disorders, and benzodiazepine intake. Multivariate regression analysis showed that diagnosis of comorbid FMDs was more likely associated with longer time lag until the final diagnosis of FMD, presence of tremor and non‐neurological comorbidities. Conclusions: Our findings highlight the need for prompt diagnosis of FMDs, given the relatively high frequency of associated neurological and non‐neurological diseases. Abstract : (a) Absolute frequency (and percentage) of functional motor disorders (FMDs) patients with one or more neurological disease. (b) Absolute frequency of patients with a neurological disease started before and after the definitive diagnosis of an FMDs. (c) Latency of FMDs onset (years) in patients with another neurological disease (OND).